2015
DOI: 10.1111/eve.12502
|View full text |Cite
|
Sign up to set email alerts
|

Mesh repair of a large traumatic lateral abdominal wall hernia in an 8‐day‐old foal

Abstract: Summary An 8‐day‐old French trotter colt was admitted with a traumatic lateral abdominal wall hernia with reducible intestinal content. A 15 cm long full thickness tear was identified in both the internal abdominal oblique and transverse abdominal muscles. This case report describes the surgical repair of the hernia using a polypropylene mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The aetiology of these abdominal wall hernias is hypothesised to be secondary to trauma causing weakening of the musculature, coupled with a sudden rise in intra-abdominal pressure (Hall 1957 During the 14-month study period reported here, the condition accounted for 1% (14 cases) of the total number of working equids hospitalised at the American Fondouk, Fez. The majority of these defects occurred in the region of the ventral lateral flank and were considered to be traumatic in origin (Hilbert et al 1978;Hanson and Todhunter 1986;Rijkenhuizen 2005;Gillam et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aetiology of these abdominal wall hernias is hypothesised to be secondary to trauma causing weakening of the musculature, coupled with a sudden rise in intra-abdominal pressure (Hall 1957 During the 14-month study period reported here, the condition accounted for 1% (14 cases) of the total number of working equids hospitalised at the American Fondouk, Fez. The majority of these defects occurred in the region of the ventral lateral flank and were considered to be traumatic in origin (Hilbert et al 1978;Hanson and Todhunter 1986;Rijkenhuizen 2005;Gillam et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…During the 14‐month study period reported here, the condition accounted for 1% (14 cases) of the total number of working equids hospitalised at the American Fondouk, Fez. The majority of these defects occurred in the region of the ventral lateral flank and were considered to be traumatic in origin (Hilbert et al 1978; Hanson and Todhunter 1986; Rijkenhuizen 2005; Gillam et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation